Analisa Kebijakan Ekonomi Politik Russia Terhadap Pemerintahan Afghanistan Pasca Kemenangan Taliban Tahun 2021 - Ida Susilowati; S.Thoriq Musthofa Ahmad; Sepana Virqiyan; Azzam El Zahidin (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This paper analyzes Russia's foreign policy toward the Afghan government following the Taliban's triumph. The Taliban armed group's successful takeover of the Afghan government in Kabul without resorting to violence has sparked global political interest today. Numerous comments from countries around the world, including Russia, began to surface. The purpose of this study is to provide an in-depth examination of Russia's economic and political actions toward the Afghan government following the Taliban's triumph. The study's findings indicate that the Russian government's policy toward the Taliban government is reasonably supportive, despite the fact that Russia has not officially recognized the Taliban leadership in Afghanistan. Russia financially and diplomatically supports the Taliban in order for the Taliban's authority over Afghanistan to be acknowledged by other countries and the international community. Russian policy is inextricably linked to Russia's political and economic interests in Afghanistan, which are based on Afghanistan's geostrategic and geopolitical importance to Russia.Keywords: Russian foreign policy, Taliban victory, Russia-Afghanistan Bilateral Relations AbstrakPenelitian ini membahas tentang analisis kebijakan luar negeri Rusia terhadap pemerintahan Afghansitan pasca kemenangan Taliban. Aksi kelompok milisi Taliban yang berhasil mengambil alih pemerintahan Afghanistan di Kabul tanpa adanya pertumpahan darah, menjadi isu yang cukup menarik perhatian politik global saat ini. Berbagai respon dari negara-negara di dunia mulai muncul, termasuk di antaranya negara Rusia. Penelitian ini bertujuan untuk menganalisis secara mendalam kebijakan ekonomi dan politik Rusia terhadap pemerintahan Afghanistan pasca kemenangan Taliban. Hasil penelitian menunjukkan kebijakan pemerintah Rusia yang relatif mendukung pemerintahan taliban, meskipun Rusia belum mengakui secara resmi pemerintahan Taliban di Afghanistan. Rusia mendukung Taliban baik secara ekonomi maupun politik, agar pemerintahan Taliban atas Afghanistan di akui oleh negara-negara lain dan masyarakat global. Kebijakan Rusia tidak terlepas dari kepentingan politik dan ekonomi Rusia di Afghanistan berdasarkan letak geostrategis sekaligus geopolitik Afghanistan bagi Rusia.Kata Kunci: kebijakan luar negeri Rusia, Kemenangan Taliban, Hubungan Bilateral Russia-Afghanistan